2016
DOI: 10.3892/ol.2016.5373
|View full text |Cite
|
Sign up to set email alerts
|

HER2 overexpression reverses the relative resistance of EGFR-mutant H1975 cell line to gefitinib

Abstract: Abstract. Gefitinib is an epidermal growth factor receptor tyrosine kinase inhibitor (EGFR TKI) that has been demonstrated to be clinically useful for the treatment of patients with non-small cell lung cancer (NSCLC). However, ~50% of patients do not respond to EGFR TKI treatment through the emergence of mutations, such as T790M. Therefore, it is important to determine which patients are eligible for treatment with gefitinib. As a preferred dimerization partner for EGFR, the role of EGFR 2 (HER2) in mediating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Protein expression was studied using Western blot analysis of lysate samples of PC-9GR cells and H-1975 cells to probe the effect of NLC drug formulations on the expression of EGFR protein. PC-9GR cells possess intrinsic resistance to gefitinib, while H-1975 cells harbored the L858R and T790M mutations in the EGFR kinase domain [ 76 ]. We found that naked non-bound siRNA was practically not toxic for all studied lung cancer cells (IC 50 dose could not be measured for all available concentrations of free siRNA).…”
Section: Resultsmentioning
confidence: 99%
“…Protein expression was studied using Western blot analysis of lysate samples of PC-9GR cells and H-1975 cells to probe the effect of NLC drug formulations on the expression of EGFR protein. PC-9GR cells possess intrinsic resistance to gefitinib, while H-1975 cells harbored the L858R and T790M mutations in the EGFR kinase domain [ 76 ]. We found that naked non-bound siRNA was practically not toxic for all studied lung cancer cells (IC 50 dose could not be measured for all available concentrations of free siRNA).…”
Section: Resultsmentioning
confidence: 99%
“…EGFR-TKIs benefit NSCLC patients harboring sensitive EGFR mutations and prolong survival. However, 20-30% of NSCLC patients harboring sensitive EGFR mutations exhibit primary resistance to EGFR-TKIs (Xu et al 2016;Zhang et al 2019). Further research is needed to investigate the mechanisms of primary resistance to EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 99%